The Mediating Role of Psychological Well-being in Explaining the Effect of a Health-Promoting Lifestyle on Death Anxiety in Seniors with COVID-19 Experience - Hamidi, Roghayeh; Ghodsi, Parvaneh; Taghiloo, Sadegh (Health Nexus, 2024)
The coronavirus and its variants continue to threaten the physical and mental health of many individuals, particularly those among the elderly infected with COVID-19. The purpose of this study was to examine the mediating role of psychological well-being in explaining the impact of a health-promoting lifestyle on death anxiety among seniors with COVID-19 experience in Tehran. This descriptive, correlational study involved a population of home-dwelling men and women aged 65 to 75 years in Tehran in 2023, who had experienced COVID-19 in the past six months. A targeted sample of 400 individuals responded to the Death Anxiety Scale (Templer, 1970), the Health-Promoting Lifestyle Profile (Walker et al., 1987), and the Psychological Well-being Scale (Ryff, 1989). Structural equation modeling was employed for data analysis. The findings, obtained using confirmatory factor analysis and AMOS 24 software, indicated a good fit between the structural model and the collected data. A positive and significant relationship was found between a health-promoting lifestyle and psychological well-being, and a negative and significant relationship between a health-promoting lifestyle and death anxiety, as well as between psychological well-being and death anxiety. Indirect pathways between death anxiety, a health-promoting lifestyle, and death anxiety were also confirmed (p = .001). Based on the results of this study, it can be stated that a health-promoting lifestyle influences the death anxiety of seniors with COVID-19 experience through psychological well-being. The findings of this study can be useful for counselors, psychologists, and health professionals.